Avaliação e calibração de um osteodensitômetro para estimação da composição química corporal e composição de tecidos dissecados de suínos - Silva, Marcos Kipper da (2015)
A series of studies have been developed to evaluate and calibrate a bone densitometry device (Dual-energy X-ray Absorptiometry DXA) as an indirect method for body, carcass, and pork evaluation. Thus, the technology was tested for its precision in repeatability and reproducibility conditions. The effect of the sample edge, temperature, and thickness of the sample, and the effect of modifying the composition of the sample by the addition of tissue were also tested. In addition, software packages were evaluated. Finally, a protocol was developed to calibrate the method estimating the chemical composition of entire body and half carcass; and the dissected tissue composition of half carcass and primary cuts. The repeatability and reproducibility of the equipment were in general satisfactory; however, some regions of interest should be avoided, such as the trunk. The reduction of the edge perimeter did not change the results provided by the device. The temperature had a slight effect on the results; however, a wide variation in temperature is necessary to generate a small change in DXA results. The thickness variation of a sample with constant composition was one of the factors that most influenced the DXA measurements. For this reason, the techniques for standardization considering this factor are crucial to enable this device utilization. The evaluated software were Total body and Small Animal, each one with its three configurations totaling six studies. Both software could be used to estimate the composition of dissected tissues; however, the more extensive was the dissection the lower was the accuracy of the method. Thus, estimating an amount of a particular tissue in a half carcass was more accurate than estimating the same tissues in the primal cuts. The calibration procedure allowed obtaining translation models with good accuracy and precision to estimate the chemical composition and dissected tissues. In addition, measurements took in a condition could be used to estimate the composition in another one. However, when the measurement was more specific then greater was the precision of estimation. Accurate results were achieved after small methodological adjustments. This happened because the factors affecting DXA measurements were quantified and easily corrected with method standardization. The DXA is an important tool for animal evaluation. Thus, DXA should be considered in future studies.